Water use behaviors and water access in intermittent and continuous water supply areas during the COVID-19 pandemic. (24th November 2021) - Kumpel, Emily; Billava, Nayaran; Nayak, Nayanatara; Ercumen, Ayse
Abstract: More than one billion people worldwide receive intermittent water supply (IWS), in which water is delivered through a pipe network for fewer than 24 h/day, limiting the quantity and accessibility of water. During the COVID-19 pandemic, stay-at-home orders and efforts to limit contact with others can affect water access for those with unreliable home water supplies. We explored whether water service delivery and household water-use behaviors changed during the COVID-19 pandemic in Hubballi–Dharwad, India, and whether they differed if households had IWS or continuous (24×7) water supply through a longitudinal household survey in 2020–2021. We found few perceived differences in water service delivery or water access, although one-quarter of all households reported insufficient water for handwashing, suggesting an increased demand for water that was not satisfied. Many households with 24×7 supply reported water outages, necessitating the use of alternative water sources. These findings suggest that water demand at home increased and households with IWS and 24×7 both lacked access to sufficient water. Our findings indicate that water insecurity negatively affected households' ability to adhere to protective public health measures during the COVID-19 pandemic and highlight the importance of access to uninterrupted, on-premise water during public health emergencies. HIGHLIGHTS: Water access in households with intermittent and continuous piped water supply was compared during the COVID-19 pandemic. Households reported using more water during the pandemic and having insufficient water for handwashing. Social distancing while using public water points and toilets was often infeasible. Access to uninterrupted on-premise water should be ensured during public health emergencies.